Biotic and abiotic constraints to a plant invasion in vegetation communities of Tierra del Fuego - Rauber, Ruth Bibiana (2013)
The biotic resistance theory relates invader success to species richness, and predicts that, as species richness increases, invasibility decreases.The relationship between invader success and richness, however, seems to be positive at large scales of analysis, determined by abiotic constraints, and it is to be expected that it is negative at small scales, because of biotic interactions. Moreover, the negative relationship at small scales would be stronger within species of the same functional group, because of having similar resource exploitation mechanisms. We studied the relationship between the cover of a worldwide invader of grasslands, Hieracium pilosella L., and species richness, species diversity and the cover of different growth forms at two different levels of analysis in 128 sites during the initial invasion process in the Fuegian steppe, Southern Patagonia, Argentina. At regional level, the invader was positively correlated to total (r = 0.28, P = 0.003), exotic (r = 0.273, P = 0.004), and native species richness (r = 0.210, P = 0.026), and to species diversity (r = 0.193, P = 0.041). At community level, we found only a weak negative correlation between H. pilosella and total richness (r = -0.426, P = 0.079) and diversity (r = -0.658, P = 0.063). The relationship between the invader and other species of the same growth form was positive both at regional (r = 0.484, P < 0.001) and community (r = 0.593, P = 0.012) levels. Consequently, in the period of establishment and initial expansion of this exotic species, our results support the idea that invader success is related to abiotic factors at large scales of analysis. Also, we observed a possible sign of biotic constraint at community level, although this was not related to the abundance of species of the same growth form.